Philosophy 167: Class 1 - Part 2 - Basic Astronomy: The Celestial Sphere. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: This video provides a brief introduction to astronomy.; Opening line: "So let's start looking at this. How did we first come to have high quality evidence in any of the sciences? Interestingly enough, it comes almost entirely from the evidence in question, comes almost entirely from the skies."; Duration: 8:50 minutes.; Segment: Class 1, Part 2.